IMPLEMENTATION OF INNOVATIVE TEACHING METHODS ON ENHANCING QUALITY TEACHING AND LEARNING IN SECONDARY SCHOOLS IN MOROGORO TANZANIA - George John (Nurul Jadid University, 2024)
The phenomenon of social and technological development has brought significant changes in the world of education, particularly in teaching practices. However, in Tanzania, the adoption of innovative teaching methods in secondary schools is still limited. This study aims to explore teachers' awareness of innovative teaching methods and their application in the context of secondary education in Morogoro, Tanzania. The research approach used is qualitative, aimed at understanding the patterns of innovative method usage and the factors influencing them. The research results show that most teachers have theoretical awareness of innovative teaching methods, such as blended learning and mobile learning, but their implementation is still low due to infrastructure and training limitations. Students acknowledge that these methods enhance engagement and flexibility in learning, although their implementation is not yet uniform across all schools. Thus, it can be concluded that there is an urgency for the professional development of teachers through continuous training and the provision of adequate infrastructure to support the implementation of innovative teaching methods.